Occupational Health and Safety Risk Analysis in Construction Projects: A Systematic Literature Review - Desy Mei Dina; Aleksander Purba (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2022)
The construction service business world always wants the best results in every project activities carried out. One of the best desired outcomes is the timely completion of a construction project, but this is often not achieved for several reasons, one of which is occupational health and safety incidents that occurs in a construction project. Based on the background of the problem and the results of a literature review sourced from 40 journals from 2011-2021, the journals collected and reviewed discussed occupational health and safety in construction projects. Therefore, it is very necessary to implement an OHS (Occupational Health and Safety) management system during construction work. Occupational health and safety aims to create conditions that support work comfort for workers, so as to improve risk management. Using sources based on previous research, the following will identify the types of occupational safety and health risk factors that most often occur in construction work. The types of risks that will be discussed here will be divided into three types based on internal risk, external risk, and project risk. Types of risk are divided into two types, namely technical and non-technical risks. Based on data from a total of 40 studies that have been reviewed, there are 22 studies that have Project Risk as the risk that causes 76% of risk in a building construction project.